1982
DOI: 10.1021/ma00230a020
|View full text |Cite
|
Sign up to set email alerts
|

Random coil configurations of aromatic polyesters: temperature coefficient of the unperturbed dimensions of poly(diethylene glycol terephthalate) chains

Abstract: Hydroxyl-terminated poly(diethylene glycol terephthalate) chains having number-average molecular weights of 7200 were end-linked into noncrystallizable trifunctional networks using an aromatic triisocyanate. The networks thus obtained were studied with regard to their stress-strain isotherms at 62, 70, and 88 °C. For elongation ratios up to 400% none of the isotherms displayed an increase or upturn in the reduced forces [/*], indicating that the polymer does not crystallize under stress, probably due to very u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Rotational angles about O-CH2 bonds of the ester and ether groups were considered to be located at12 0, ±104°a nd13 0, ±100°, respectively, whereas for CH2-CH2 bonds these angles were assumed to be13 0, ±120°; furthermore, 0-C*0* bonds of the ester groups are restricted to a trans conformation.14 As for the conformational energies associated with the rotational states, they are described in detail elsewhere.13-18 Briefly, gauche states about O-CH2 bonds of the ester and ether groups have energies of 0.4 and 0.9 kcal mol-1, respectively, above those of the corresponding trans states,13-17 whereas the energy of gauche states about CH2-CH2 bonds adjacent to the ester groups is 0.8 kcal mol-1 below that of the corresponding trans. [14][15][16] Gauche states about the central CH2-CH2 bonds of the repeating unit were assumed to be preferred by only 0.5 kcal mol-1 over the alternative trans states. Second-order interactions of C*0*-0, CH2-0, and CH2-CH2 groups were considered to be 1.4, 0.6, and » 2 kcal mol-1, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Rotational angles about O-CH2 bonds of the ester and ether groups were considered to be located at12 0, ±104°a nd13 0, ±100°, respectively, whereas for CH2-CH2 bonds these angles were assumed to be13 0, ±120°; furthermore, 0-C*0* bonds of the ester groups are restricted to a trans conformation.14 As for the conformational energies associated with the rotational states, they are described in detail elsewhere.13-18 Briefly, gauche states about O-CH2 bonds of the ester and ether groups have energies of 0.4 and 0.9 kcal mol-1, respectively, above those of the corresponding trans states,13-17 whereas the energy of gauche states about CH2-CH2 bonds adjacent to the ester groups is 0.8 kcal mol-1 below that of the corresponding trans. [14][15][16] Gauche states about the central CH2-CH2 bonds of the repeating unit were assumed to be preferred by only 0.5 kcal mol-1 over the alternative trans states. Second-order interactions of C*0*-0, CH2-0, and CH2-CH2 groups were considered to be 1.4, 0.6, and » 2 kcal mol-1, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…They indicate that the free rotation is not a good approximation for the calculation of Kerr constants; however, it is not = 120°(i.e., rotational isomers placed at 0, ±120°). 6 Set I, conformational energies taken from ref 11. c Set II, conformational energies of ref 13.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…Recently, the conformational characteristics of PDET as well as the elastic behavior of model networks prepared from this polymer were examined. [11][12][13][14] It was found that although most of the skeletal bonds of the repeat unit are either restricted to trans states or show preference for these states, the high preference for gauche states of the two remaining skeletal C-C bonds confers on this polymer a high degree of flexibility, so that these molecules are more coiled than was suspected initia1ly.l Moreover, the evidence at hand indicates that the accessibility of PDET chains to different spatial arrangements should not be hindered by constraints such as might result from chain crystallization, at least for moderately high e10ngations.l~ Poly(diethy1ene glycol terephthalate) networks exhibit rubberlike behavior above room temperature, with essentially complete recovery even in the cases in which relatively large deformations can be accomplished. An important feature of these networks is that for elongation ratios a >5, an increase in the modulus or an upturn appears in the Mooney-Rivlin p10ts.l~ Since small crystallites usually act as reinforcers, preventing crack growth in the networks,15 the anomalous increase of the modulus was attributed to strain-induced crystallization.…”
Section: Introductionmentioning
confidence: 99%